2021
DOI: 10.1038/s41598-021-00350-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prewarming on body temperature in short-term bladder or prostatic transurethral resection under general anesthesia: A randomized, double-blind, controlled trial

Abstract: Perioperative hypothermia causes postoperative complications. Prewarming reduces body temperature decrease in long-term surgeries. We aimed to assess the effect of different time-periods of prewarming on perioperative temperature in short-term transurethral resection under general anesthesia. Randomized, double-blind, controlled trial in patients scheduled for bladder or prostatic transurethral resection under general anesthesia. Eligible patients were randomly assigned to receive no-prewarming or prewarming d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The effectiveness of these precautions, owing to the reduced core-to-periphery gradients, has been confirmed in previous studies. [27][28][29] This study showed that the change in the peripheral temperature (axillary temperature) coincided with the change in the core temperature (lower esophagus temperature), but with a 15-min lag. The explanation may involve the following: (1) as anesthesiarelated hypothermia mainly stems from core-to-periphery heat dissipation, 18 there existed an earlier decrease in the core temperature and (2) the water mattress was near the peripheral temperature monitoring site, so the site was more susceptible to heating.…”
Section: Discussionmentioning
confidence: 65%
“…The effectiveness of these precautions, owing to the reduced core-to-periphery gradients, has been confirmed in previous studies. [27][28][29] This study showed that the change in the peripheral temperature (axillary temperature) coincided with the change in the core temperature (lower esophagus temperature), but with a 15-min lag. The explanation may involve the following: (1) as anesthesiarelated hypothermia mainly stems from core-to-periphery heat dissipation, 18 there existed an earlier decrease in the core temperature and (2) the water mattress was near the peripheral temperature monitoring site, so the site was more susceptible to heating.…”
Section: Discussionmentioning
confidence: 65%
“…It is e cient and convenient, and recommended to be actively used in clinical practice [21][22][23]. Regarding to the warming period, some evidence suggests that extending systemic warming to the preoperative period could be more bene cial than limiting it only to during surgery [24][25][26]. The decrease in body temperature starts just after anesthesia induction due to heat redistribution from core to peripheral compartments [27].…”
Section: Discussionmentioning
confidence: 99%
“…IIH is one of the most prevalent events faced by anaesthesiologists, with a current prevalence of 20%-70%, [1][2][3][4] even up to 90% decades ago. 5,6 It is a risk factor for a series of postoperative complications, including bleeding and blood product transfusion, 7,8 cardiovascular events, 9,10 postoperative infection, 10,11 shivering, 12 drug metabolism disorder, 13 prolonged stay in the postanaesthetic recovery unit 14 and increased length of hospital stay, 10,11,15 etc. All of these unfavourable consequences lead to increased hospitalisation expense, [16][17][18] patient discomfort, and complains.…”
Section: Introductionmentioning
confidence: 99%